2007
DOI: 10.1080/10934520701435585
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of arsenic and antimony in soils from an abandoned mining area, Glendinning (SW Scotland)

Abstract: The mobility and bioavailability of As and Sb in relation to soil-biota transfer were evaluated at a former Sb mining and smelting site (Glendinning, SW Scotland, UK). The study specifically assessed the accumulation of As and Sb in different environmental components (soil, plants and earthworms) across mining area to estimate risk factors for the biota. Total concentrations and fractions of As and Sb in soils were determined. The latter using both a single solute and a non-specific stepwise sequential extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 61 publications
2
20
1
Order By: Relevance
“…However, only a few studies in the literature were devoted to differences in uptake of Sb and As by plants. One study in a mine contaminated area in Glendinning, Scotland showed that Sb was proportionally more available, whereas biological uptake by plants (ferns and grass) and earthworms was higher for As (Gál et al, 2007). In contrast, our chemical fractionation data show that Sb at the Příbram site was found to be chemically less mobile (Figs.…”
Section: Sources and Distribution Of Sb And Ascontrasting
confidence: 77%
See 2 more Smart Citations
“…However, only a few studies in the literature were devoted to differences in uptake of Sb and As by plants. One study in a mine contaminated area in Glendinning, Scotland showed that Sb was proportionally more available, whereas biological uptake by plants (ferns and grass) and earthworms was higher for As (Gál et al, 2007). In contrast, our chemical fractionation data show that Sb at the Příbram site was found to be chemically less mobile (Figs.…”
Section: Sources and Distribution Of Sb And Ascontrasting
confidence: 77%
“…The application of SEP on polluted soil and sediment samples from Mansfeld District, Germany, showed that up to 18% of the As and 12% of the Sb was extracted in the first step, corresponding to the "mobile" fraction (Müller et al, 2007). The only contrasting results were found in soils from an old mining area in Glendinning, Scotland, where 1 mol l − 1 NH 4 NO 3 extraction yielded higher amounts of mobile Sb (0.01-8.8% of total Sb) than mobile As (0.01-0.6% of total As) (Gál et al, 2007).…”
Section: Implications For the Mobility Of Sb And Asmentioning
confidence: 81%
See 1 more Smart Citation
“…Ore smelting took place at Jamestown, ~1 km downhill of the mine (Gallagher et al, 1983). Several spoil heaps in the vicinity of the mine are still evident, and previous studies have reported Sb concentrations of 14.0-673 mg kg −1 (Flynn et al, 2003) and 10.3-1200 mg kg −1 (Gál et al, 2007) in the surrounding soils. Whilst these studies demonstrated that the soil Sb concentrations were significantly elevated above background levels, the geochemical associations, lateral and vertical elemental mobility and transport mechanisms for Sb, As and Pb at the site remain poorly defined.…”
Section: Introductionmentioning
confidence: 96%
“…Significant environmental and human health impacts are associated with on-going ore extraction and smelting processes but there are also environmental concerns relating to historical sites. In the UK, Sb mining and smelting activities ceased in the mid-20th century (Flynn et al, 2003) but impacts upon soils and waters are still observed in the 21st century (Flynn et al, 2003;Gál et al, 2007). In addition, Sb mining and smelting processes usually release arsenic (As) and lead (Pb) to the environment since all three elements commonly co-occur in the sulfidic ore deposits.…”
Section: Introductionmentioning
confidence: 99%